Interrogating the Responses of WHO to the Outbreak of Covid-19 in Nigeria - Folorunso, Gideon Ibukuntomiwa; Duruji , Moses Metumara; Chidozie, Felix C.; Osimen, Goddy Uwa (Journal of Ecohumanism, 2024)
The study introduces the World Health Organization as the apex body of global health, which is charged with the fundamental role of maintaining a healthy globe. However, outbreak of diseases has become a growing menace that the WHO has battled for decades since its inception. COVID-19 is the latest of such battles. This study employs ex post facto research design with qualitative approach. Using the textual analysis, this study interrogated the responses of the WHO with regards to the outbreak of COVID-19 in Nigeria. Some of these responses include technical aids, training aids, among other active responses. These responses, however, cannot be achieved without the role of the apex national health institution, the Nigeria Centre for Disease Control and Prevention (NCDC). The study shows that the effectiveness of NCDC in contact tracing, surveillance, intelligence gathering, partnerships and collaborations, and so forth, was paramount to the successes achieved post-pandemic. The study recommended the improvement of political, economic, and technological interventions, in a way that there is adequate preparedness for future outbreaks. Proposed the adoption of Health Systems Strengthening, and the adoption of horizontal healthcare approach, rather than the currently operational vertical healthcare approach. The study offers a holistic perspective on COVID-19 pandemic management in Nigeria, which focused points on best practices to improve preparedness for future outbreaks.